Disassembly Modeling of an of End-Of-Life (EOL) Mechanical Damper for Recycling - Simolowo, Oluwafunbi Emmanuel; Olalekan, Akintunde (Transactions on Engineering and Computing Sciences, 2017)
Today’s rapidly developing technologies and product designs have enabled manufacturers to deliver new products to consumers at a dramatic rate. This has in turn resulted in shorter lifespan for products, because, more often than not, they are discarded even though they are still in excellent working conditions. An overflowing stream of used scrapped products has become an alarming problem for waste management, as it is quickly elevating the level of environmental detriments. Countries around the world have also observed an explosive growth in the waste stream that is filling up municipal landfills and clogging up incinerators. These problems, in addition to the limited material resources on Earth have made the recycling of End-Of-Life (EOL) products a rapidly expanding research area. However, before recycling of EOL products can be done, they need to be disassembled. Therefore, this paper focuses on the automation of disassembly of EOL car dampers that are found wasting away in many auto repair workshops. It discusses the application of the component-mating graph and newer CAD methods in the disassembly modeling of an EOL mechanical damper.